Catalytic Cooperation between a Copper Oxide Electrocatalyst and a Microbial Community for Microbial Electrosynthesis. Issue 5 (11th May 2021) - Chatzipanagiotou, Konstantina‐Roxani; Soekhoe, Virangni; Jourdin, Ludovic; Buisman, Cees J. N.; Bitter, J. Harry; Strik, David P. B. T. B.
Abstract: Electrocatalytic metals and microorganisms can be combined for CO2 conversion in microbial electrosynthesis (MES). However, a systematic investigation on the nature of interactions between metals and MES is still lacking. To investigate this nature, we integrated a copper electrocatalyst, converting CO2 to formate, with microorganisms, converting CO2 to acetate. A co‐catalytic (i. e. metabolic) relationship was evident, as up to 140 mg L −1 of formate was produced solely by copper oxide, while formate was also evidently produced by copper and consumed by microorganisms producing acetate. Due to non‐metabolic interactions, current density decreased by over 4 times, though acetate yield increased by 3.3 times. Despite the antimicrobial role of copper, biofilm formation was possible on a pure copper surface. Overall, we show for the first time that a CO2 ‐reducing copper electrocatalyst can be combined with MES under biological conditions, resulting in metabolic and non‐metabolic interactions. Abstract : The combination of metal and biological electrocatalysts for CO2 conversion in one reactor is reported in this work. Microorganisms grew in suspension and as biofilm on a formate‐producing copper electrode, and elongated the available substrates (CO2, formate) to acetate. Both metabolic and non‐metabolic effects were observed between the two catalysts. Overall, microbial activity was enhanced by the presence of a formate‐producing copper catalyst.